Dųhų ası k’ëch’á – Things Are Changing: Climate Change, Afforestation, and Indigenous Economic Opportunity in Northern Saskatchewan - Kayseas, Bob; Baldwin, Katharine B. (Journal of Aboriginal Economic Development, 2025)
Indigenous communities in Northern Canada face rapid climate change that threatens their local ecosystems, food security, cultural ties to the land, and connections to the rest of Canada. Participating in climate adaptation efforts is crucial for Indigenous well-being, self-determination, and economic involvement amid a changing climate. We interviewed a total of 11 people drawn from the Elders, land users, community leaders, Indigenous business owners, and nonprofit staff at Black Lake, Fond du Lac, and Hatchet Lake Denesųłiné First Nations in Northern Saskatchewan. For over 40 years, these knowledge holders observed how climate change threatened their communities’ traditional practices and the Denesųłiné way of life. They also discussed various adaptive measures that could bolster local economic development. In this paper, we present community perspectives on one specific climate adaptation action: high-latitude tree line afforestation. While community members are concerned that afforestation could harm wildlife (especially barren-ground caribou), be undertaken without local consent and control, and facilitate the spread of invasive species, they also hope that an afforestation project could create jobs, involve youth, support the local economy, and contribute to fighting climate change.